The Role of Trade Literature in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1990, examines the relationship between sci-tech materials and trade literature, commonly called manufacturers’ catalogues. Because very little has been published about the value and nature of trade literature in regard to sci-tech libraries, this volume is important in informing librarians about a little-known segment of the larger picture of sci-tech information sources, thus adding to the value of their services to their clients.